The potential for Indigenous-led conservation in urbanized landscapes in Canada - Moola, Faisal; Jolly, Helina; Borah, Joli; Roth, Robin (Frontiers in Human Dynamics, 2024)
Indigenous Protected and Conserved Areas (IPCAs) are an important pathway and governance system for area-based conservation led by Indigenous Peoples. While IPCAs have been established across rural and northern regions of Canada, they have received little attention in urbanized landscapes, even though all of Canada’s urban areas coincide with First Nations, Inuit, and Métis territory (and thereby underlying Indigenous jurisdiction) and the majority of Indigenous Peoples in the country live in urban centers. Canada’s federal government is in the process of establishing six new urban national parks and has committed to working with local Indigenous governments and organizations in parks planning. This study examined the potential for strengthening Indigenous participation in urban parks planning, governance, and management, including the establishment of new urban Indigenous Protected and Conserved Areas (UIPCAs). The results of spatial analyses of urban Indigenous territory, a review of relevant domestic and international policy and interviews with local Indigenous conservation leaders illuminate the potential for new forms of urban conservation governance that are grounded in Indigenous rights and responsibilities and reflective of Indigenous knowledge systems and biocultural priorities. However, it remains to be seen how urban Indigenous-led conservation, such as UIPCAs, can fit and operate within proposed government urban conservation initiatives, such as Canada’s Urban National Parks Program, which do not currently foreground Indigenous-led conservation in the governance of urban green space.